Bivariate and Multivariate NeuroXidence: A Robust and Reliable Method to Detect Modulations of Spike–Spike Synchronization Across Experimental Conditions - Wu, Wei; Wheeler, Diek W.; Pipa, Gordon (Frontiers in Neuroinformatics, 2011)
Synchronous neuronal ﬁring has been proposed as a potential neuronal code. To determine whether synchronous ﬁring is really involved in different forms of information processing, one needs to directly compare the amount of synchronous ﬁring due to various factors, such as different experimental or behavioral conditions. In order to address this issue, we present an extended version of the previously published method, NeuroXidence. The improved method incorporates bi- and multivariate testing to determine whether different factors result in synchronous ﬁring occurring above the chance level. We demonstrate through the use of simulated data sets that bi- and multivariate NeuroXidence reliably and robustly detects joint-spike-events across different factors.